Almitrine for COVID-19 critically ill patients – a vascular therapy for a pulmonary vascular disease: Three case reports - Huette, Pierre (World J Clin Cases, 2021)
BACKGROUND: Several reports with clinical, histological and imaging data have observed the involvement of lung vascular function to explain the severe hypoxemia in coronavirus disease 2019 (COVID-19) patients. It has been hypothesized that an increased pulmonary blood flow associated with an impairment of hypoxic pulmonary vasoconstriction is responsible for an intrapulmonary shunt. COVID-19 may lead to refractory hypoxemia (PaO(2)/FiO(2 )ratio below 100 mmHg) despite mechanical ventilation and prone positioning. We hypothesized that the use of a pulmonary vasoconstrictor may help decrease the shunt and thus enhance oxygenation. CASE SUMMARY: We report our experience with three patients with refractory hypoxemia treated with almitrine to enhance oxygenation. Low dose almitrine (Vectarion(®); Servier, Suresnes, France) was started at an infusion rate of 4 μg × kg/min on a central line. The PaO(2)/FiO(2 )ratio and total respiratory system compliance during almitrine infusion were measured. For the three patients, the PaO(2)/FiO(2 )ratio time-course showed a dramatic increase whereas total respiratory system compliance was unchanged. The three patients were discharged from the intensive care unit. The intensive care unit length of stay for patient 1, patient 2 and patient 3 was 30 d, 32 d and 31 d, respectively. Weaning from mechanical ventilation was performed 13 d, 18 d and 15 d after almitrine infusion for patient 1, 2 and 3, respectively. We found no deleterious effects on the right ventricular function, which was similar to previous studies on almitrine safety. CONCLUSION: Almitrine may be effective and safe to enhance oxygenation in coronavirus disease 2019 patients. Further controlled studies are required.